Enhanced Mechanical Properties of 3D Printed Concrete Sculpture Material with Wood Fibers Reinforcement - Muhammad Fadhil Wong bin Abdullah (Tanjung Malim, 2024)
Enhanced Mechanical Properties of 3D Printed Concrete Sculpture Material with Wood Fibers Reinforcement by Muhammad Fadhil Wong bin Abdullah